Australia‐wide cross‐sectional survey of general practitioners' knowledge and practice of lung cancer screening. Issue 7 (18th July 2021) - Abeyweera, Prarthana Dharshanie; Brims, Fraser J. H.; Piccolo, Francesco; Lei, Cory; Manners, David
Abstract: Background: Low‐dose computed tomography (LDCT) screening can reduce lung cancer deaths in high‐risk individuals, yet current Australian guidelines do not recommend screening. Little is known about current screening practices in Australia. Aim: To evaluate the proportion of general practitioners who report ordering lung cancer screening for their patients, identify factors associated with ordering lung cancer screening and assess general practitioners (GP) rationale for recommending screening and preference of composition of any future national targeted screening programme. Methods: A survey was distributed to a nationally representative sample of 4000 Australian GP. The questionnaire included respondent demographics, self‐reported screening practices, knowledge of screening recommendations, recent screening education, preference for recruitment methodologies for potential screening programmes and potential factors influencing the screening practices of GP. Two logistic regression models identified factors associated with self‐reported chest X‐ray (CXR) and LDCT screening within the past 12 months. Results: A total of 323 GP completed the survey (participation rate 8.1%). Participants were mostly females (50.6%), from collective/group (79.1%) and metropolitan‐based practices (73.5%). Despite the majority of responders understanding that screening is not recommended by Australian professional societies (71.2%), a substantial proportion of participants requested a CXR or LDCT screening (46.4% and 20.8% respectively). A variety of shared (GP reassurance, affordability of screening, believing screening is funded) and unique practice, educational and cognitive factors were associated with self‐reported LDCT and CXR screening, with the strongest association being recent education about screening from radiology practices (odds ratio (aOR) for LDCT screening 10.4, P < 0.001). Conclusion: In Australia, lung cancer screening occurs outside a coordinated programme, and there is discordance between practice and national recommendations. This highlights an urgent need for clearer guidance from national and professional bodies.